Synthesis, characterization and antibacterial activity of mono-, di- And tri-tosylate of glycerol - Yusof, Y.A.; Ariffin, Azhar (Penerbit Universiti Kebangsaan Malaysia, 2016)
Glycerol is a valuable co-product from oleochemical industry such as from fatty acid and biodiesel production. By having three hydroxyl groups in its molecule, glycerol can undergo chemical modifications that lead to many possible applications. This paper reports the tosylation process of glycerol with para-toluenesulfonyl chloride (p-TsCl). Reaction of glycerol with p-TsCl in the presence of a base produced mono-, di- And tri-tosylate of glycerol even though the reaction was carried out at the mole ratio of 1.2:1.0 of glycerol to p-TsCl. The compounds were successfully isolated and characterized. Mono-, di- And tri-tosylate of glycerol exhibited inhibitory activity against Staphylococcus aureus (gram positive bacteria) and Pseudomonas aeruginosa (gram negative bacteria).